2010
DOI: 10.1002/syn.20827
|View full text |Cite
|
Sign up to set email alerts
|

An approach for serotonin depletion in pigs: Effects on serotonin receptor binding

Abstract: Depletion of central serotonin (5-HT) levels and dysfunction in serotonergic transmission are implicated in a variety of human CNS disorders. The mechanisms behind these serotonergic deficits have been widely studied using rodent models, but only to a limited extent in larger animal models. The pig is increasingly used as an experimental animal model especially in neuroscience research. Here, we present an approach for serotonin depletion in the pig brain. Central serotonin depletion in Danish Landrace pigs wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…The in vitro autoradiography confirmed high binding of both [ 18 F]MH.MZ and [ 18 F]altanserin in the pig cerebral cortex in accordance with previous results (Ettrup et al, ). Whereas ketanserin blocked [ 18 F]MH.MZ binding in the pig frontal cortex completely, some NSB of [ 18 F]altanserin remained in white matter, which is in contrast to expectations based on the higher lipophilicity of MH.MZ as compared with altanserin (Herth et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The in vitro autoradiography confirmed high binding of both [ 18 F]MH.MZ and [ 18 F]altanserin in the pig cerebral cortex in accordance with previous results (Ettrup et al, ). Whereas ketanserin blocked [ 18 F]MH.MZ binding in the pig frontal cortex completely, some NSB of [ 18 F]altanserin remained in white matter, which is in contrast to expectations based on the higher lipophilicity of MH.MZ as compared with altanserin (Herth et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…[ 18 F]MH.MZ and [ 18 F]altanserin distribution in pig brain slices (Fig. ) was in accordance with the expected 5‐HT 2A receptor distribution (Ettrup et al, ). The K d value of [ 18 F]MH.MZ for 5‐HT 2A receptors in pig frontal cortex was determined to be 8.4 ± 5.9 nM (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Obesity in humans is associated with lower cerebral 5-HT levels (Bjorntorp, 1995;Strombom et al, 1996), implying that the receptor may be insufficiently stimulated to reduce the drive to eat. Furthermore, 5-HT depletion was found to significantly increase 5-HT 4 R binding in NAc in pigs (Ettrup et al, 2011) and we therefore speculate that the higher 5-HT 4 R level in NAc may be a compensatory upregulation due to the lower 5-HT levels and further that the receptor requires a higher endogenous stimulation to elicit satiety. Insufficient 5-HT 4 R signaling could also in turn result in lower 5-HT levels in NAc, given that CART stimulates 5-HT release in NAc, either via direct excitatory effects of CART on serotonergic terminals in NAc or by serotonergic projections from the dorsal raphe nuclei (Ma et al, 2007).…”
Section: Normal Weightmentioning
confidence: 69%
“…Interestingly, evidence suggests that 5-HT 4 receptor levels are influenced by changes in availability of 5-HT. In particular, an earlier study reported that a 5-HT neuronal lesion increased the abundance of 5-HT 4 receptor binding sites in rat brain (Compan et al 1996b), and more recently inhibition of 5-HT synthesis by p-chlorophenylalanine (pCPA) was found to increase 5-HT 4 receptor binding in both pig and rat brain (Ettrup et al 2011 ;Licht et al 2009). Conversely, repeated administration of selective inhibitors of 5-HTT, which increase extracellular 5-HT availability, decreased the density of 5-HT 4 receptor binding sites and also reduced 5-HT 4 receptor function (Licht et al 2009 ;Vidal et al 2009).…”
Section: Introductionmentioning
confidence: 99%